Modeling and control of the nonlinear quater car model for active suspension system - 396437 Norlela Ishak (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Kejuruteraan (Elektrik - Mekatronik dan Kawalan Automatik)) - Universiti Teknologi Malaysia, 2006